(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
Sixteen Roman artefacts were presented to the Society by George Clark in December 1857 along with a list of where they were found. The article contains this list, a page with illustrations of some of the artefacts, and a short biography of the Sir John Clerk, the eighteenth-century antiquarian who collected the objects.